Penerapan Teknologi Web Service Pada Sistem Informasi Data Rekam Medis Rumah Sakit XYZ - Triawan Adi Cahyanto (Query: Journal of Information Systems, 2018)
Data processing system of inpatient medical records is one of the functions of the administration in providing services to patients to meet the demands, both for management of the hospital, patients, and paramedics. Hospitals in small urban areas are generally still doing manual processing (simple still be processing data in the handwritten form printed in report form archives). Based on these problems, we need solutions to make medical record information system using web services technology. Web service technology have used to synchronize data between the subunits in the hospital. Systems built using services more than one database that could be accessed via WSDL service and the data format used is XML. Services available for access are data search services and data detail services.Keywords: Information System, Medical Records, Web Service, Hospitals